«Завойовники» Юрія Яновського: автор у пошуках назви твору - Кондратьєва, С. (Слово і Час, 2021)
У статті розглянуто варіанти назви, які Ю. Яновський підбирав для
п’єси «Завойовники», та принципи їх добору. Досліджено чернетки письменника як джерело назв, проаналізовано епізоди й деталі, що не ввійшли
до п’єси, але мали вплив на появу її окремих заголовків. Звернено увагу на
зв’язок варіантів назви безпосередньо зі змістом твору і з позатекстовою реальністю. Результати дослідження показують, що Ю. Яновський
розглянув понад тридцять варіантів, перш ніж обрати заголовок «Завойовники». Їх аналіз, а також розгляд пов’язаних із ними чернеток дає
підстави припустити, що автор намагався знайти назву, яка б найкраще акцентувала наскрізну ідею твору. Велика кількість варіантів
була зумовлена не тільки ретельним творчим пошуком, а й тим, що
Ю. Яновський почав добирати назву для п’єси на ранньому етапі, коли
сюжет і головна ідея ще не були остаточно сформовані. The titles of Yurii Yanovskyi’s plays have not been studied yet. There are research works dealing
with different issues of his plays and focusing on the titles of his novels but not plays. The
present paper analyzes different variants of the title that Yanovskyi had for his play finally
called “Zavoiovnyky” (“The Conquerors”). The writer’s purpose was to find a name that
would most accurately reflect the idea and emphasize the main theme of his work. The author
was focused on two topics while writing the play. The first one was war and fight, and
the second was international consciousness and unification of the working class. The writer
had considered more than thirty optional titles before he chose the final one. It is important
to note that Yanovskyi had started creating variants of the title before the text of the play
was finished. Therefore, some options had been related to the themes that finally were not
manifested in the play, or at least were not presented in scale sufficient for giving ground to
the correspondent names. Some of the variants were not only related to the themes of the
play but also directly referred to some episodes, sometimes omitted in the final version and
kept only in the draft s. Some optional titles implied a wider metaphorical sense. The last
approach is relevant for the final title “Zavojovnyky” as well. With this word Yanovskyi
didn’t name a physical conquest of some land by some people, but the expansion of the idea
of uniting the working class around the globe. The author directly expressed this idea in the
final monologue of his play, with the statement that the working class aims to conquer all
the world.